Expression of thrombospondin-1 by tumor cells in patient-derived ovarian carcinoma xenografts. (3rd September 2015) - Pinessi, Denise; Ostano, Paola; Borsotti, Patrizia; Bello, Ezia; Guffanti, Federica; Bizzaro, Francesca; Frapolli, Roberta; Bani, Maria Rosa; Chiorino, Giovanna; Taraboletti, Giulia; Resovi, Andrea
Abstract: Purpose : Thrombospondin-1 (TSP-1), a major regulator of cell interaction with the environment, is often deregulated in cancers, including ovarian carcinoma. Both the tumor and the host cells can release TSP-1 in the tumor microenvironment. The relative contribution of the two sources in determining TSP-1 levels in ovarian cancer remains to be elucidated. This study was designed to investigate the expression of tumor TSP-1 in a panel of 29 patient-derived ovarian adenocarcinoma xenografts (PDX), using analytical tools specific for human (tumor-derived) rather than murine (host-derived) TSP-1. Methodology : Human-specific microarray and ELISA were used to measure tumor TSP-1 expression and plasma levels. Results : Tumor-derived TSP-1 was heterogeneously expressed in PDX. Expression was higher in the corresponding original patient's tumor, where stroma-derived TSP-1 is also analyzed, indicating that both the tumor and the host contribute to TSP-1 production. TSP-1 was differentially expressed according to tumor grade, but not affected by p53 expression or mutational status. Findings were confirmed in an external gene expression dataset (101 patients). In a functional enrichment analysis, TSP-1 correlated with genes related to angiogenesis, cell motility, communication and shape. Plasma TSP-1, detectable in 10/11 PDX, was not associated to its expression in the tumor. The possible association of plasma TSP-1 with p53 mutations and response to chemotherapy warrants further investigation. Conclusions : Ovarian carcinoma PDX are a useful tool to investigate the relative contribution of stroma and tumor cells in the production of tumor associated factors, in relation to the tumor behavior, molecular properties and response to therapy.